Acre 1291 bloody sunset of the Crusader states - Nicolle, David 1944- (Campaign (Osprey Publishing), 2005)
In April 1291, a Mamluk army laid siege to Acre, the last great Crusader fortress in the Holy Land. For six weeks, the siege dragged on until the Mamluks took the outer wall, which had been breached in several places. The Military Orders drove back the Mamluks temporarily, but three days later the inner wall was breached. King Henry escaped, but the bulk of the defenders and most of the citizens perished in the fighting or were sold into slavery. The surviving knights fell back to their fortress, resisting for ten days, until the Mamluks broke through. This book depicts the dramatic collapse of this great fortress, whose demise marked the end of the Crusades in the Holy Land.